Gukurahundi, Media and the “Wounds of History”: Discourses on Mass Graves, Exhumations and Reburials in Post-Independent Zimbabwe - Ndlovu, Mphathisi (Journal of Literary Studies, 2021)
Graves are central to Zimbabwe’s political landscape since they constitute sites of contestation in respect of memory and identity. Given the legacies of the Gukurahundi genocide, it is fitting to examine the debates and controversies surrounding the Zimbabwean government’s plans to exhume the remains of victims from mass graves. In 1983 the Robert Mugabe led government deployed a military unit (the Fifth Brigade) to the Matabeleland and Midlands provinces, supposedly to quash a “dissident” movement. The military unit went on to commit unspeakable crimes against civilians. By the time the Gukurahundi genocide ended in 1987, at least 20 000 Ndebele speaking people had been killed. Memories of these horrendous crimes remain repressed and heavily guarded by the state, though there are increasing calls for justice, as well as calls to commemorate and rebury the victims of the Gukurahundi genocide. Recently, the government has been advocating the “fast track” exhumation and reburial of Gukurahundi victims. However, some civic groups in Matabeleland are resisting this state engineered mechanism of exhumation and social healing. Given that mass graves represent “crime scenes” and “wounds of history”, this article investigates the politics of memory triggered by the government’s planned exhumation of Gukurahundi victims from mass graves. It explores how discourses on the exhumation of genocide victims from mass graves are mediated and contested in spaces of communication, such as news websites and Twitter. This article, which is informed by Achille Mbembe’s theorisation of necropolitics, concludes that mass graves and bodily remains connected to the Gukurahundi genocide constitute symbolic representations of the ongoing political struggles in Zimbabwe. The government’s attempt to appropriate, to manage and to control the Gukurahundi exhumations and reburials demonstrates its reaffirmation of necropolitics, which is an effort by the regime to obscure the massacre, to obliterate evidence and to legitimise its sovereignty. However, the government’s power is not absolute since there is resistance from civic movements and ordinary people who regard the mass graves as evidence of the genocide, which is crucial to the pursuit of justice and accountability. Opsomming Grafte staan sentraal in Zimbabwe se politieke landskap, want dit is setels van geskille oor heugenis en identiteit. In die lig van die nalatenskap van die Gukurahundi volksmoord is dit gepas om die debatte en polemiek oor die Zimbabwiese regering se planne om die oorskot van slagoffers uit massagrafte op te grawe, te ondersoek. In 1983 het die regering, onder leiding van Robert Mugabe, ’n militere eenheid (die Vyfde Brigade) na Matabeleland en die Middellande ontplooi om ’n sogenaamde dissidente beweging hok te slaan. Die militere eenheid het onbeskryflike misdade teen burgerlikes gepleeg. Minstens 20 000 Ndebele sprekende mense is doodgemaak teen die tyd dat die Gukurahundi volksmoord in 1987 tot ’n einde gekom het. Herinneringe van hierdie afgryslike wandade word steeds onderdruk en streng deur die staat in bedwang gehou, maar daar is toenemende oproepe om geregtigheid, tesame met versoeke dat die slagoffers van die Gukurahundi volksmoord gedenk en herbegrawe word. Die regering het onlangs onthul dat hy beoog om die oorskot van Gukurahundi slagoffers by wyse van ’n bespoedigde proses te laat opgrawe en herbegrawe. Sommige burgerlike groepe in Matabeleland bied egter weerstand teen hierdie staatsgemanipuleerde meganisme van opgrawing en maatskaplike heling. Aangesien massagrafte “misdaadtonele” en “wonde van die geskiedenis” verteenwoordig, ondersoek hierdie artikel die politiek van heugenis waartoe die regering se beoogde opgrawing van die oorskot van Gukurahundi slagoffers uit massagrafte aanleiding gee. Dit ondersoek hoe diskoerse oor die opgrawing van volksmoordslagoffers uit massagrafte in kommunikasieruimtes, soos nuuswebtuistes en Twitter, bemiddel en aangevoer word. Hierdie artikel, wat Achille Mbembe se teoretisering van nekropolitiek as grondslag het, kom tot die slotsom dat massagrafte en liggaamlike oorskot wat met die Gukurahundi volksmoord verband hou, die voortslepende politieke stryd in Zimbabwe versinnebeeld. Die regering se poging om die opgrawing en herbegrawing van Gukurahundi slagoffers toe te eien en beheer daarvan te neem, dui op sy herbevestiging van nekropolitiek, wat neerkom op ’n poging deur die regime om die volksmoord te verdoesel, bewyse te vernietig en sy soewereiniteit te bekragtig. Die regering se mag is egter nie absoluut nie aangesien hy teenstand kry van burgerlike bewegings en gewone mense wat van mening is dat die massagrafte as bewys dien van die volksmoord wat plaasgevind het, wat uiters belangrik is vir die strewe na geregtigheid en toerekenbaarheid.